Pengaruh Pengembangan Karyawan Dan Kompensasi Kerja Terhadap Kinerja Karyawan Melalui Budaya Organisasi Di PT. SGS Indonesia - Widyaningrum, Shafiena; Tabroni; Derriawan (JURNAL EKONOMI, MANAJEMEN, BISNIS, DAN SOSIAL (EMBISS), 2023)
The objective of this research is to analyze the effect of people development and compensation employee and organizational culture through Performance in PT. SGS Indonesia. In this research data collection using the questionnaire collected from respondents. The sampling method collection used in this research is non-probability sampling, with a collection technique of purposive sampling. The total sample of this research is 130 respondents. The analysis used in this research is Structural Equation Modelling (SEM) analysis techniques, a method for hypothesis testing using the software LISREL. The results of this research showing that People Development has a significant impact on Organization Culture, Compensation has a significant impact on Organization Culture, People Development has a significant impact on Performance, Compensation has a significant impact on Performance, and Organization culture has a significant impact on Performance